"There was Sex but no Sexuality*:" Critical Cataloging and the Classification of Asexuality in LCSH. Issue 6 (17th August 2020) - Watson, Brian M.
Abstract: This paper examines the addition of "asexuality" to the Library of Congress Subject Headings as a case study from which to examine the critical cataloging movement. Beginning with a review of some of the theoretical and practical issues around subject access for minoritized and marginalized sexualities, this paper then contextualizes, historicizes, and introduces the critical cataloging movement to the literature, situating it within a larger and longer history of radical cataloging. It will define critical cataloging as a social justice-oriented style of radical cataloging that places an emphasis on radical empathy, outreach work, and recognizes the importance of information maintenance and care. This paper introduces the concept of "catalogic warrant" to characterize the process of "reading" the catalog to examine the harm or benefit of terms on users and the wider library community.